Unsymmetrical Bisquinolines with High Potency against P. falciparum Malaria - Liebman, Katherine M. (Molecules, 2020)
Quinoline-based scaffolds have been the mainstay of antimalarial drugs, including many artemisinin combination therapies (ACTs), over the history of modern drug development. Although much progress has been made in the search for novel antimalarial scaffolds, it may be that quinolines will remain useful, especially if very potent compounds from this class are discovered. We report here the results of a structure-activity relationship (SAR) study assessing potential unsymmetrical bisquinoline antiplasmodial drug candidates using in vitro activity against intact parasites in cell culture. Many unsymmetrical bisquinolines were found to be highly potent against both chloroquine-sensitive and chloroquine-resistant Plasmodium falciparum parasites. Further work to develop such compounds could focus on minimizing toxicities in order to find suitable candidates for clinical evaluation.